Intestinal Paracoccidioidomycosis: Case report and systematic review - Cruz,Eduarda Renz da (2021)
ABSTRACT Background: Paracoccidioidomycosis is a systemic mycosis considered endemic and limited to Latin America with the majority of registered cases originating from Brazil. The purpose of this paper was to report a case of a female patient with paracoccidioidomycosis mimicking inflammatory bowel disease and to systematically review available cases of the intestinal presentation of this infectious disease. Case report: Female patient, 32-years old, previously asymptomatic, presenting with acute pain in the lower right abdomen, associated with signs of peritoneal irritation and abdominal distension. Urgent surgery was performed, which identified a severe suppurative perforated ileitis. The anatomopathological study revealed fungal structures shaped as a ship’s pilot wheel in Grocott-Gomori’s staining, suggestive of Paracoccidioides spp. Methods: Studies were retrieved based on Medical Subject Headings and Health Sciences Descriptors, which were combined using Boolean operators. Searches were run on the electronic databases Scopus, Web of Science, MEDLINE (PubMed), BIREME (Biblioteca Regional de Medicina), LILACS (Latin American and Caribbean Health Sciences Literature), SciELO (Scientific Electronic Library Online), Embase, and Opengray.eu. Languages were restricted to English, Spanish and Portuguese. There was no date of publication restrictions. The reference lists of the studies retrieved were searched manually. Simple descriptive analysis was used to summarize the results. Results: Our search strategy retrieved 581 references. In the final analysis, 34 references were included, with a total of 46 case reports. The most common clinical finding was abdominal pain and weight loss present in 31 (67.3%) patients. Most patients were treated with itraconazole (41.3%) and amphotericin B (36.9%). All-cause mortality was 12.8%. Conclusions: Paracoccidioidomycosis should be suspected in endemics areas, specially as a differential diagnosis for inflammatory bowel disease. Endoscopic tests and biopsy are useful for diagnosis and treatment with antifungal drugs seem to be the first treatment option to achieve a significant success rate.